MUSIC FOR DAIRY CATTLE: ITS IMPACT ON PHYSIOLOGICAL CONDITIONS, BEHAVIOR, AND MILK PRODUCTION—A REVIEW - Nasihin, Ahmad; Kurniawan, Farhan Fadhli (Jurusan Peternakan Fakultas Pertanian Universitas Pattimura, 2025)
Music, as a form of environmental enrichment, has considerable potential to enhance the welfare and productivity of dairy cattle. This study aimed to synthesize and analyze research findings from the past decade regarding the effects of music exposure on the physiological conditions, behavior, and milk production of dairy cattle. A literature review methodology was employed, involving the collection of scientific articles, theses, and conference proceedings published between 2015 and 2025, followed by descriptive analysis. The findings indicate that several studies have reported slow-tempo music typically 70–100 beats per minute (BPM), which measures beat frequency, and volumes below 70 decibels (dB), which quantify sound intensity, can reduce stress hormones such as cortisol, elevate serotonin levels, enhance feed consumption and feed efficiency, improve milking behavior, and increase milk production. However, other studies have also reported no significant effects or adverse outcomes associated with using fast-tempo or high-volume music. These inconsistencies highlight the need for more standardized research that considers factors such as individual cow variability, environmental conditions, and variations in music delivery methods. Music presents a promising, innovative, and animal-friendly strategy for improving dairy farm performance, although its successful implementation depends on stronger and more consistent scientific validation.